A central limit theorem for realised power and bipower variations of continuous semimartingales - Ole Eiler Barndorff-Nielsen; Svend Erik Graversen; Jean Jacod; Mark Podolskij (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
Central limit theorem, quadratic variation, bipower variation
Keywords: 519; Central limit theorem; quadratic variation; bipower variation; Martingale; Zeitreihenanalyse; Theorie